2014
DOI: 10.1074/jbc.m114.556175
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Elucidation of a New α-Conotoxin, Lo1a, from Conus longurionis

Abstract: Background: ␣-Conotoxins are small toxins produced by cone snails and antagonists of nicotinic acetylcholine receptors. Results: Two mutants were created to investigate the unusual C terminus of a novel ␣-conotoxin from Conus longurionis. Conclusion: We characterized an important residue for discrimination between neuronal and muscle subtype nicotinic acetylcholine receptors. Significance: This opens perspectives for designing new ligands to affect brain disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…The target fraction is concentrated, applied on a cation/anion exchange chromatography column and eluted in accordance with the basicity of the peptide. Reverse phase C18 HPLC with an additional step of rechromatography on the same column for excluding impurities will be used for final purification [ 24 , 25 ].…”
Section: Procedures For Isolating Marine Peptidesmentioning
confidence: 99%
“…The target fraction is concentrated, applied on a cation/anion exchange chromatography column and eluted in accordance with the basicity of the peptide. Reverse phase C18 HPLC with an additional step of rechromatography on the same column for excluding impurities will be used for final purification [ 24 , 25 ].…”
Section: Procedures For Isolating Marine Peptidesmentioning
confidence: 99%
“…nAChRs are situated in the plasma membranes of certain neurons in the central and peripheral nervous systems [1]. These ligand-gated ion channels are involved in signal transmission, neuronal integration and cell excitability through activation by acetylcholine (ACh) binding [1].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Giribaldi et al revealed that CIA also blocked the neuronal rat α3β2 nAChR with micromolar potency [43]. As we know, α-4/7-conotoxin was generally regarded as targeting various neuronal nAChRs, however, one α-4/7-conotoxin EI isolated from Conus ermineus was identified as selectively targeting the α/δ interface of the Torpedo muscle-type nAChRs [44], another α-4/7-conotoxin Lo1a has been characterized to differentiate between muscle-type nAChRs and neuronal-type nAChRs, and this conotoxin had a higher affinity at the α/ε interface [45]. Interestingly, αA-conotoxin OIVB with six cysteines isolated from Conus obscurus venoms from Indo-Pacific, exhibited 1800-fold lower affinity for adult muscle nAChRs, and this toxin preferentially bound to the α/γ interface [46].…”
Section: Discussionmentioning
confidence: 99%